A MULHER NO MERCADO DE TRABALHO: CONQUISTAS, DESAFIOS E PERSPECTIVAS NA CONTEMPORANEIDADE (REMUNOM, 2025)
This study investigates the integration of women into the labor market and the transformations that have occurred throughout history, analyzing changes in female social roles and the challenges that persist. Based on a literature review, it is observed that despite advancements in professional inclusion, women still face wage disparities, occupational segregation, and difficulties in reaching leadership positions. Moreover, the burden of balancing professional life with personal issues such as motherhood and workplace harassment remains a significant obstacle. The study highlights the need for public policies and cultural changes to promote gender equity in the labor market.